A Randomized Phase I Evaluation of CTP‐499, a Novel Deuterium‐Containing Drug Candidate for Diabetic Nephropathy1. Issue 1 (21st February 2013) - Braman, Virginia; Graham, Philip; Cheng, Changfu; Turnquist, David; Harnett, Mark; Sabounjian, LuAnn; Shipley, James
Abstract To determine maximum tolerated dose and food effect for CTP‐499, a novel agent being studied for the treatment of diabetic kidney disease. CTP‐499 has demonstrated anti‐inflammatory, anti‐fibrotic and anti‐oxidative activities in vitro as well as anti‐inflammatory and renoprotective effects in a diabetic nephropathy (DN) model. Two studies were performed. Study 1 was a single‐dose escalation study with 600, 1200, 1800, and 2400 mg doses of controlled‐release (CR) CTP‐499 and a 400 mg immediate release dose to aid in the development of prototype formulations of CTP‐499. Study 2 was a food‐effect study. Plasma concentrations of CTP‐499 and its metabolites were measured to determine pharmacokinetic parameters in each study. Safety was assessed to determine tolerability. Doses up to and including 1800 mg were well tolerated. Cmax was either equivalent (CTP‐499) or slightly lower (metabolites) for the fed condition, while overall exposure was equivalent (CTP‐499) or slightly higher (metabolites) for the fed condition. The range of tolerated doses of CTP‐499 and the effects of food on exposure were identified, contributing to selection of the dose for Phase II development.